COVID Longa não prejudica as respostas hemodinâmicas, vasculares ou autonômicas ao exercício máximo: estudo estratificado por sexo em adultos jovens - Rodrigues, Carla Nascimento dos Santos (Universidade Federal de São Carlos, 2025)
Long COVID (LC) is a multisystemic post-viral condition, prevalent among females, and frequently associated with fatigue, exercise intolerance, and autonomic dysfunction. Although clinical reports suggest residual cardiovascular impairments, few studies employing standardized methodologies have investigated, in a sex-stratified manner, the physiological responses to maximal exercise-induced stress. This study aimed to analyze hemodynamic, autonomic, and functional responses during and up to 24 hours after a cardiopulmonary exercise test (CPET) in young adults with and without LC, with an emphasis on sex-related differences. This was an observational, controlled, and stratified study, approved by the Research Ethics Committee of the Federal University of São Carlos (CAAE: 65086622.5.0000.5504). A total of 38 young adults participated (18 LC and 20 controls [CON]), categorized by biological sex as female (F) and male (M): LC-F, LC-M, CON-F, and CON-M. The protocol included hemodynamic and autonomic monitoring at rest, during, and after CPET, as well as 24-hour ambulatory blood pressure monitoring (ABPM). The following variables were assessed: systolic and diastolic blood pressure (SBP and DBP), heart rate (HR), cardiac output (CO), pulse wave velocity (PWV), augmentation index (AIx@75%), heart rate variability (HRV), and peak oxygen consumption (VO₂peak). Measurements were collected at rest, at exercise peak, and at multiple recovery time points (immediately, 3, 5, 10, 30, 60 minutes, and 24 hours post-exercise). Female participants were evaluated between the late follicular and mid-luteal phases of the menstrual cycle, with 75% using oral hormonal contraceptives. Statistical analyses were performed using R software (v.4.1.2), employing Student’s t-tests, Mann–Whitney U tests, two- and three-way repeated-measures ANOVA with Tukey’s correction. Normality and homogeneity were verified using the Shapiro–Wilk and Levene tests, respectively. Results were expressed as mean ± SD and 95% CI, with effect size (Cohen’s d) and a significance level of p < 0.05. The results showed that the main physiological differences were more closely associated with biological sex than with clinical status (LC vs. CON). At rest, no significant differences were observed among groups for most hemodynamic or functional variables. The primary distinction emerged during post-exercise recovery. The only variable differing between clinical groups was the 24-hour mean SBP, which was lower in the LC-F subgroup compared with CON-F (104.0 ± 13.3 vs. 107.3 ± 11.5 mmHg; p = 0.027). In conclusion, in this sample of physically active young adults, the presence of LC did not result in clinically relevant alterations in cardiovascular, autonomic, or functional responses to maximal exercise. Biological sex emerged as the main modulator of physiological responses, underscoring the importance of sex stratification in studies of post-viral conditions.
Long COVID does not impair hemodynamic, vascular, or autonomic responses to maximal exercise: sex-stratified study in young adults
Keywords: Pós-Pandemia; Estresse Fisiológico; Monitoramento Ambulatorial; Recuperação Subaguda; Dimorfismo Sexual; Post-Pandemic; Ambulatory Monitoring; Subacute Recovery; Sexual Dimorphism; CIENCIAS BIOLOGICAS::FISIOLOGIA; 3. Saúde e Bem-Estar